Lightweight Django using rest, websockets, & backbone - Elman, Julia; Lavin, Mark (O'Reilly Media, 2015)
Through a series of rapid application development projects, this hands-on book shows experienced Django developers how to include REST APIs, WebSockets, and client-side MVC frameworks such as Backbone.js into new or existing projects.